2008
DOI: 10.1007/s12272-001-1215-4
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of bis, tris and tetra(dihydrocaffeoyl)polyamine conjugates as antibacterial agents against VRSA

Abstract: Bis, tris and tetra(dihydrocaffeoyl)polyamine conjugates were synthesized using solid phase synthesis technique. These compounds were screened for antibacterial activity against methicillin-resistant Staphylococcus aureus (MRSA) (11 strains) and vancomycin-resistant S. aureus (VRSA) (4 strains). Bis, tris and tetra(dihydrocaffeoyl)polyamine analogues showed antibacterial activity against VRSA which were better than the reference drugs, vancomycin. Tetra(dihydrocaffeoyl)polyamine conjugate exhibited the highest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…By analysis of the NMR spectroscopic data and comparison with the literature, the known compounds were respectively identified as N 1 , N 10 -bis(dihydrocaffeoyl)spermidine ( 2 ) [ 12 ], N - trans -coumaroyltyramine ( 3 ) [ 13 ], N - trans -feruloyltyramine ( 4 ) [ 14 ], N - trans -feruloyl 3′-O-methyldopamine ( 5 ) [ 15 ], N - trans -feruloyloctopamine ( 6 ) [ 14 ], N - cis -coumaroyltyramine ( 7 ) [ 16 ], N - cis -feruloyltyramine ( 8 ) [ 14 ], and N - cis -feruloyloctopamine ( 9 ) [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…By analysis of the NMR spectroscopic data and comparison with the literature, the known compounds were respectively identified as N 1 , N 10 -bis(dihydrocaffeoyl)spermidine ( 2 ) [ 12 ], N - trans -coumaroyltyramine ( 3 ) [ 13 ], N - trans -feruloyltyramine ( 4 ) [ 14 ], N - trans -feruloyl 3′-O-methyldopamine ( 5 ) [ 15 ], N - trans -feruloyloctopamine ( 6 ) [ 14 ], N - cis -coumaroyltyramine ( 7 ) [ 16 ], N - cis -feruloyltyramine ( 8 ) [ 14 ], and N - cis -feruloyloctopamine ( 9 ) [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…The elucidation and specific assignments of these compounds were in supporting information. Other known compounds are isolated as scopolamine3940 ( 1 ), anisodamine4142 ( 2 ), hyoscyamine4344 ( 3 ), anisodine31 ( 4 ), N-Caffeoylputrescine364546 ( 14 ), N1,N10-di-dihydrocaffeoylspermidine2147 ( 17 ), Scotanamine D21 (19), and N1-caffeoyl-N3-dihydrocaffeoyl spermidine48 ( 20 )…”
Section: Resultsmentioning
confidence: 99%
“…For example, spermidine hydroxycinnamate conjugates have antioxidant [31, 32], antibacterial [33], antiviral [34], insecticidal [35] and antiparasitic [36] activities. Other studies have demonstrated the inhibitory activity of polysubstituted p -coumaroyl polyamines on brain transporters for which a genetic polymorphism is associated with psychological disorders [37, 38].…”
Section: Resultsmentioning
confidence: 99%